Ecotoxicidade do inseticida Malathion e seus efeitos sobre os biomarcadores ensaio cometa e acetilcolinesterase em Daphnia magna - Knapik, Luís Felipe Onisanti (2018)
Malathion, an organophosphate insecticide, presents high toxicity and is one of the most used in the world. Daphnia magna is a world-wide used microcrustacean in ecotoxicological studies, to analyze the acute toxicity of liquid effluents and chemical substances. Biomarkers are responses that live organisms exhibit after contamination and have, as an advantage, the early detection of damage and the potential to assess the magnitude of contamination and degree of severity of effects. In the literature, we found several biomarkers employing different test organisms, however, few studies are using biomarkers in D. magna. In this sense, the present study investigated the acute ecotoxicity (EC50 determination) and the genetic and neurotoxic effects of the insecticide malathion on D. magna, through the comet assay and evaluation of the activity of the enzyme acetylcholinesterase, respectively, in the sublethal concentrations of 1.26 10-3 ng L-1 and 4.7 10-4 ng L-1. The comet assay, was performed by gel electrophoresis of cells obtained from D. magna after disaggregation of the newborn organisms, with damage reading done visually in an epifluorescence microscope. The enzymatic activity of extracts (obtained after unbundling of the neonates) was measured by reading in microplate reader at 405 nm for 5 min. The acute ecotoxicity of the compound for D. magna presented an EC50 (48h) of 1.26 10-3 ng L-1, indicative of extreme ecotoxicity. Through the comet assay, damage to the genetic material of organisms exposed to malathion was observed, and significant difference (p<0.05) between the concentrations tested and the control groups. The enzymatic activity presented a significant difference (p<0.05) between controls and the concentration 4.7 10-4 ng L-1. These results demonstrate the high ecotoxicity and ability to harm genetic material and neurotoxicity to neonates even at below-ambient concentrations.